Pengaruh Pemberian Ekstrak Etanol Kakao (Theobroma cacao) terhadap Kadar Malondialdehida Tikus Wistar Jantan Model Fraktur Tulang (The Effect of Cocoa Ethanolic Extract (Theobroma cacao) on Malondialdehyde of Male Rattus novergicus Bone - Anas Bakhtiar Diyansah; Erma Sulistyaningsih; Muhammad Hasan (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Fracture is a serious musculoskeletal trauma. The healing process of fracture is disturbed by the oxidative stress, because of imbalance quantity of Reactive Oxygen Species (ROS) and an antioxidant. An antioxidant such as polyphenol, that can be found in cocoa, is needed to suppress oxidative stress. The study aimed to investigate the effect of cocoa ethanolic extract on decreasing oxidative stress by measuring malonaldialdehyde (MDA) concentration in fracture healing process. Trial test were conducted in eleven rats to determine appropriate plaster technique. The study used thirty rats and divided into five groups; the normal group without fracture, the negative control group and three treatment groups with manually fractured on left tibia under anaesthesia and immobilized by leucodur plaster. Each treatment group was treated with cocoa ethanolic extract in a dose of 125 mg/kgBW, 250 mg/kgBW, or 500 mg/kgBW orally, respectively for 21 days. The result showed that there was a significant effect of cocoa ethanolic extract on serum and bone MDA concentration in which MDA concentration decreased after cocoa ethanolic extract treatment. The study concluded that cocoa ethanolic extract had a positive effect on supression of oxidative stress in fracture healing process. Keywords: Cocoa ethanolic extract, polyphenol, fracture healing process, MDA, ROS